(untitled) (Herald of Journalism, 2020)
In the Article said that journalism connects with the society. If the so- ciety is democratic, Journalism is also democratic and the demand to the journalism is very big. In the article the author observed that democracy is a main value and journalist must be intelligent and think about innovation in journalism.